Enhancing Educational Innovation in Underdeveloped Regions: A Management Model for Enhancing Entrepreneurial Competence in NTT Schools - Rosita Indrawati; Murpin Josua Sembiring; Liliana Dewi (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study examines the systemic obstacles to entrepreneurship education in East Nusa Tenggara (NTT), one of Indonesia's most underdeveloped provinces. Rural institutions like SMPN 2 and SMPN 7 Sambi Rampas encounter significant obstacles: 83% of educators are untrained in entrepreneurship pedagogy, and only 21% of schools have access to entrepreneurial resources or local business networks. This research seeks to develop a pragmatic, context-sensitive educational model that enhances entrepreneurial skills among rural students. The study uses a qualitative approach involving four informants comprising school leaders, teachers, parents, and students through interviews, focus group discussions, and document analysis to derive grounded insights. Research indicates that adaptive school leadership, teacher peer mentoring, and parental engagement directly impact the success of student-led microbusiness initiatives. A notable revelation deemed a “Stunning Finding” is that women-led student cooperatives in these isolated regions surpass conventional school-operated business programs regarding sustainability, participation rates, and local innovation. Experiential and problem-based learning make this innovation model viable and replicable in under-resourced communities. It contests the belief that entrepreneurial success necessitates urban infrastructure, emphasising that inclusive, community-based educational models can convert rural schools into centres of innovation and resilience. The study concludes with a proposed framework for school-based entrepreneurship that emphasises leadership, collaboration, and gender-inclusive practices within rural education systems